SKRINING EKSTRAK JAMUR ENDOFIT DARI TANAMAN MELINJO (Gnetum gnemon L.) SEBAGAI KANDIDAT ANTIBAKTERI, ANTIJAMUR DAN ANTIOKSIDAN - Muhlisun Azim; Puspawan Hariadi; Yuyun Febriani; Tri Puspita Yuliana (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2022)
Endophytic fungi are potential microorganisms in lead compounds investigation as research objects for antibacterial and antifungal drug candidates. These microorganisms are able to produce various secondary metabolites, moreover they can even be regulated according to the needs of researchers. This is an advantage of endophytic fungi with good adaptability response. This study aims to explore the antibacterial, antifungal and antioxidant activity of endophytic fungi from the branch of the Melinjo tree (Gnetum gnemon L.) by qualitative analysis. This study resulted in 13 potential endophytic fungi extracts to be explored further for their compounds. Based on the results of the TLC test of the fungal extracts with 10% vanillin in H2SO4 as a reagent, it showed that the dominant compounds were alkaloids and polyphenols. The antibacterial activity test of extracts of the endophytic fungi was carried out by the disc diffusion agar method against Staphylococcus aureus and Pseudomonas aeruginosa bacteria, while antifungal agents were used for Candida albicans and Aspergillus clavatus.. Meanwhile, the qualitative test of antioxidants from fungal extracts using the DPPH spray reagent showed positive results of 8 fungal extracts. Screening of endophytic fungi from melinjo represented a source of endophytes potential as antibacterial, antifungal and antioxidant to be developed in exploration of secondary metabolites from natural products of microbial.